2011
DOI: 10.19030/cier.v4i3.4116
|View full text |Cite
|
Sign up to set email alerts
|

Review Of Gender Differences In Learning Styles: Suggestions For STEM Education

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 20 publications
0
37
0
1
Order By: Relevance
“…Essential considerations include sex, age, culture and race/ethnicity, learning styles, emotional status, readiness to learn, readiness to change, developmental stage, literacy, and self-efficacy. [12][13][14][15][16][17] Kulturel-Konak and colleagues 14 found that women prefer hands-on learning experiences, make intuitive or feeling-based judgments, are more people-oriented, and more comfortable with ambiguity. Educational interventions are also more effective when the teaching is learner-centered and individualized.…”
Section: Essential Considerations In Designing and Implementing Nursimentioning
confidence: 99%
See 1 more Smart Citation
“…Essential considerations include sex, age, culture and race/ethnicity, learning styles, emotional status, readiness to learn, readiness to change, developmental stage, literacy, and self-efficacy. [12][13][14][15][16][17] Kulturel-Konak and colleagues 14 found that women prefer hands-on learning experiences, make intuitive or feeling-based judgments, are more people-oriented, and more comfortable with ambiguity. Educational interventions are also more effective when the teaching is learner-centered and individualized.…”
Section: Essential Considerations In Designing and Implementing Nursimentioning
confidence: 99%
“…13,16 Fundamental nursing care aspects producing successful behavioral change outcomes include consistent patient monitoring, scheduling regular follow-up and healthcare support (eg, education, counseling), control of substance abuse, such as alcohol and smoking, individualized dietary regimen, including fat, salt, fruit, and vegetable intake along with medication regimen monitoring and adjustment to manage BP. [9][10][11][12][13][14][15] Results from Chiu and Wong's randomized control trial further revealed that nurse-run clinics have positive effects on BP control, and adherence to health lifestyle and follow-up telephone call reinforce the coaching efforts of nurse clinical consultations. 15 Another 2014 nursing study targeting adults with AF emphasized the importance of individualized patient education to achieve positive outcome for older adults who had cognitive, as well as functional, limitations.…”
Section: Essential Considerations In Designing and Implementing Nursimentioning
confidence: 99%
“…A small sampling of this includes: [1][2][3][4][5][6][7]. In addition to this, considerable work has been done to determine how to best meet the differing needs of the two genders in the classroom.…”
Section: Introductionmentioning
confidence: 99%
“…6 There are also distinctions between learning preferences based on gender. 7 Because the correspondence between learning preference and learning environment has a significant impact on learning outcomes, it is important to consider the implications of different learning styles by gender.…”
Section: Different Preferences For Learning By Gendermentioning
confidence: 99%
“…Kulturel-Konak, D'Allegro, and Dickinson yielded similar findings in a study of learning preferences of over 300 undergraduate students. 7 Across STEM and non-STEM majors, a key finding was that women prefer collaboration and cooperation over competition, which is favored by men. Additionally, women favored creative materials; whereas men mostly wanted concrete materials, which is most commonly used in classroom instruction.…”
Section: Different Preferences For Learning By Gendermentioning
confidence: 99%